Evaluating Multimedia and Language Tasks - Soboroff, Ian; Awad, George; Butt, Asad; Curtis, Keith (Frontiers in Artificial Intelligence, 2020)
Evaluating information access tasks, including textual and multimedia search, question answering, and understanding has been the core mission of NIST’s Retrieval Group since 1989. The TRECVID Evaluations of Multimedia Access began in 2001 with a goal of driving content-based search technology for multimedia just as its progenitor, the Text Retrieval Conference (TREC) did for text and web.